Biodiesel production from Terminalia bellerica using eggshell-based green catalyst: An optimization study with response surface methodology - Akshey Marwaha; Pali Rosha; Saroj Kumar Mohapatra; Sunil Kumar Mahla; Amit Dhir (Energy Reports, 2019)
The main aim of this study was to find the possibility of biodiesel production from Terminalia bellerica and evaluation of optimal input reaction parameters (molar ratio, reaction temperature and catalyst amount) for maximizing the methyl ester yield with Box-Behnken design. Calcium oxide catalyst synthesized from waste chicken eggshells was used for conversion of Terminalia bellerica oil. Highest yield of 97.98% was achieved with optimized parameters: 62.5 °C temperature, 2.25 wt. % catalyst amount and 9:1 molar ratio where the agitation speed of the stirrer during reaction was kept constant at 600 rpm. The fuel properties of Terminalia bellerica methyl ester such as acid value 0.030 mg KOH/g, kinematic viscosity 4.722 cSt, flash point 160 °C, pour point 0 °C, cetane number 52 and oxidative stability 2.2h were within the limits of ASTM 6751 and EN14214 specifications.
Keywords: 330; Biodiesel; Box-Behnken; Eggshell; Fuel; RSM